The relative efficacy of topical non-steroidal anti-inflammatory drugs and capsaicin in osteoarthritis - Persson, Monica S.M. (2019)
Background Pain is often the most troubling issue for people with osteoarthritis (OA) and is typically the focus of pharmacological management. A multitude of treatment options are available for OA, but these produce, on average, only small to moderate reductions in pain. Often the modest reductions in pain do not outweigh the safety concerns of traditional analgesics. Topical non-steroidal anti-inflammatory drugs (NSAIDs) and capsaicin are safe alternatives, with different mechanisms of action, that are widely used for knee and hand OA. However, there is a paucity of evidence to guide the choice between the treatments. Their relative efficacies are unknown and it is unclear if certain people would benefit more from one treatment than the other. The identification of predictors of response to the treatments is essential in order to maximise treatment effects and implement a precision medicine approach in OA care.